1980
DOI: 10.1093/carcin/1.12.975
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of the transplacental blastomogenic effect of nitrosomethylurea by postnatal administration of buformin to rats

Abstract: N-Nitrosomethylurea (NMU) (20 mg/kg) was i.p. administered to rats on the 21st day of pregnancy. A decrease of glucose utilisation in the oral glucose tolerance test was found in 3 month old female progeny of NMU-treated rats. The serum insulin level did not differ from control, but serum cholesterol level was higher in offspring of NMU-treated rats. The ability of diethylstilboestrol to inhibit compensatory ovarian hypertrophy was decreased in female hemicastrated 3 month old rats whose mothers were treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
2

Year Published

1982
1982
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 0 publications
2
12
0
2
Order By: Relevance
“…A decrease of glucose utilization in the oral glucose tolerance test was found in the 3-month-old female progeny of rats exposed to NMU on the 21 st day of pregnancy [201]. The serum insulin level was not different from the control, but the cholesterol level was higher in offspring of NMU-treated rats as compared with the control.…”
Section: Pharmacological Modulation Of Gh/insulin/igf-1 Signaling mentioning
confidence: 99%
“…A decrease of glucose utilization in the oral glucose tolerance test was found in the 3-month-old female progeny of rats exposed to NMU on the 21 st day of pregnancy [201]. The serum insulin level was not different from the control, but the cholesterol level was higher in offspring of NMU-treated rats as compared with the control.…”
Section: Pharmacological Modulation Of Gh/insulin/igf-1 Signaling mentioning
confidence: 99%
“…Antidiabetic biguanides have been proposed for the prevention of the age-related increases of cancer and atherosclerosis and for the retardation of the aging processes [12,21]. It was shown that administration of phenformin lowers blood cholesterol, triglyceride, and ß-lipoprotein levels in patients with hyperlipidemia, inhibits the development of atherosclerosis, reduces hyperinsulinemia in men with coronary artery disease, increases hypothalamopituitary sensitivity to inhibition by dexamethasone, causes restoration of the estrous cycle in persistent-estrous old rats, improves cellular immunity in atherosclerotic and cancer patients, lowers blood somatomedin-like levels in cancer and atherosclerotic patients with type IIb hyperlipoproteinemia, inhibits mammary, colon, and transplacental carcinogenesis in rats, and prolongs the life span of mice and rats [12,22,[46][47][48][49][50][51]. It is worth noting that mutations in Caenorhabditis elegans that reduce overall insulin signaling decrease accumulation of oxidized proteins, increase MnSOD activity, decrease oxidative stress, and extend the life span [51][52][53][54].…”
Section: Antidiabetic Treatmentmentioning
confidence: 99%
“…A decrease of glucose utilisation in the oral glucose tolerance test was found in the 3-month-old female progeny of rats exposed to NMU on the 21st day of pregnancy [115]. The serum insulin level was not differ from the control, but the cholesterol level was higher in offspring of NMU-treated rats as compared with the control.…”
Section: Introductionmentioning
confidence: 99%